On ideas and economic policy: a survey of MENA economists. Issue 1 (2nd January 2020) - Hendy, Rana; Mohieldin, Mahmoud
ABSTRACT: This paper examines how economic ideas have been shaped throughout history and the influence of these on the formulation of economic policy. We collect both quantitative and qualitative data from economists who are originally from the Middle East and North Africa region or working on the region. We find that economists and their ideas are more likely to be influenced by multiple schools of thought than adhere to one school. This multiplicity spills over into the type of solutions proposed to economic problems and thus policy implications. One of the main recommendations of this study is that there is a need for the development of economics and economists to recognize the impact of political and social issues that are not easy to grasp through modeling.